Caracterização química das plantas aquáticas coletadas no reservatório de Salto Grande (Americana-SP) - Martins, D. [UNESP] (2003)
This research aimed to describe the chemical components of the following aquatic plants: Brachiaria arrecta, Eichhornia crassipes, Pistia stratiotes and Salvinia auriculata, found in a reservoir formed by Salto Grande power plant in Americana-SP, Brazil, to provide a basis for future evaluations of the biomass behavior of these species at waste points or in the reservoir. Plant samples were collected on 04/16/2002. B. arrecta showed the lowest medium contents of macro and micronutrients and the highest medium contents of heavy metal in the dry matter, compared to the other aquatic species. The C/N relationship of E. crassipes, P. stratiotes and S. auriculata showed similar contents. Molybdenum, silver, lead and mercury were not detected in any of the species studied.